The beneficial effect of tart cherry on plasma levels of inflammatory mediators (not recovery after exercise): A systematic review and meta-analysis on randomized clinical trials - Ali Gholami; Bahareh Amirkalali; Hamid Reza Baradaran; Mitra Hariri (Elsevier, 2022)
Background: Chronic inflammation has been classified as one of the most important threats to health. Scientists suggested that tart cherry (TC) can reduce plasma levels of inflammatory mediators. Therefore, the aim of this study was to summarize the effect of TC on circulating C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) among adult participants in non-exercise randomized clinical trials (RCTs). Methods and materials: The eligible English-language RCTs were found by searching databases including PubMed, Web of Science, Cochrane Library, Scopus, and clinical Trials.gov up to May 2022, with no time limit. We used the mean change from baseline and its standard deviation for both intervention and comparison groups to calculate the effect size. The random-effects model proposed by DerSimonian and Laird was used to estimate the overall summary effect and the heterogeneity. We used PRISMA 2020 guidelines to report this study. Results: Ten RCTs were included in this study. The results demonstrated that TC had a significant decreasing effect on plasma CRP level compared with the comparison group (weighted mean differences (WMD) = −0.55 mg/L; 95% confidence interval (CI): − 1.03, − 0.06; p = 0.029), but had no significant effect on plasma IL-6 compared with comparison group (WMD = 0.08 pg/mL; 95% CI: −0.02, 0.17; p = 0.10). The effect of TC consumption on plasma TNF-α level was evaluated in only three studies that showed no significant effects (p>0.05). Conclusion: Our results confirmed a significant decreasing effect of TC on CRP. Regarding IL-6 and TNF-α, our study did not present any significant effect of TC.